Career Decision-Making Difficulties: Why Exploration Alone Is Not Enough for High School Students - Simanjuntak, Janice Grace Lusiani Larasati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2024)
Career exploration is important for high school students to face career decision-making difficulties. This study aims to investigate the effect of career exploration training on career decision-making difficulties among 12th-grade high school students. A total of 24 SMAK BPPK grade 12 high school students in Bandung were divided into two matching groups (experimental group and control group) based on pretest scores measured by the Career Decision-Making Difficulties Questionnaire. Pretest and posttest scores data were analyzed using the related samples t-test. The results of this research show that there is no effect of career exploration training on career decision-making difficulties of grade 12 high school students. This research confirms that career exploration will be beneficial for career decision-making if it is accompanied by confidence and the ability to integrate various information into a decision (creative self-efficacy). This self-efficacy can be supported by parents, older siblings, or teachers.